Respuesta :
subtract L from both sides
S - L = L - L -rL
S - L = -rL
divide both sides by L
S - L/L = -rL/L
-r = S - L/L
divide both sides by -1
r = -S + L/L
S - L = L - L -rL
S - L = -rL
divide both sides by L
S - L/L = -rL/L
-r = S - L/L
divide both sides by -1
r = -S + L/L
Answer:
The value of the formula is [tex]r=\frac{L-S}{L}[/tex].
Step-by-step explanation:
Consider the provided formula.
[tex]S = L - rL[/tex]
We need to solve the provided formulafor r.
Subtract L from both side.
[tex]S-L=L-L- rL[/tex]
[tex]S-L=-rL[/tex]
Divide both sides by -L.
[tex]\frac{S-L}{-L}=\frac{-rL}{-L}[/tex]
[tex]r=\frac{-S+L}{L}[/tex]
[tex]r=\frac{L-S}{L}[/tex]
Hence, the value of the formula is [tex]r=\frac{L-S}{L}[/tex].